To solve for x in the given equation:
1. First, we can try to factor the expression on the left side of the equation. To do this, we need to find two numbers that add up to -21 and multiply to -72 (-36 x 2).
2. After some trial and error, we can see that -24 and 3 satisfy these conditions.
3. Therefore, we can write the equation as:
(2x + 3)(x - 24) = 0
4. We can set each factor equal to 0 and solve for x:
2x + 3 = 0 or x - 24 = 0
2x = -3 x = 24
x = -3/2
5. Therefore, the solutions for x are: x = 24 and x = -3/2.
2x2 – 21x – 36 = 0
1 answer